A railway local degraded adhesion model including variable friction, energy dissipation and adhesion recovery. Issue 11 (2nd November 2021) - Meacci, Martina; Shi, Zhiyong; Butini, Elisa; Marini, Lorenzo; Meli, Enrico; Rindi, Andrea
Abstract : The modelling of the wheel–rail contact is fundamental in the railway field since the contact forces directly affect vehicle dynamics, wear, safety and maintenance. In this context, the development of a realistic adhesion model able to describe degraded adhesion conditions is still an open problem because of the complex non-linear behaviour of the adhesion coefficient. To face this problem, in this work an innovative degraded adhesion model has been developed taking into account important phenomena like large sliding at the contact interface, the consequent energy dissipation and the adhesion recovery caused by the cleaning effect on the rail due to the friction forces. The new approach, based on FASTSIM algorithm and Polach theory, is numerically very efficient and has been specifically designed for multibody applications. The developed model has been validated through the comparison with experimental data related to suitable braking manoeuvres.